Characterization of Phytochemicals and Chemical Compounds of Patat Leaves (Phrynium capitatum) as Wrapping Materials for Pesor Doclang - Ahmad Fathoni (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2021)
Doclang is a typical food of Bogor. One of the compositions is “pesor” wrapped in patat leaves. Apart from being a food wrapper, patat leaves are used as traditional medicine. Research on the chemical content of patat leaves is still limited and needs to be further developed. In this study, phytochemical testing and chemical content of the extracts of n-hexane, ethyl acetate, and methanol from patat leaves were carried out. Phytochemical tests include alkaloid tests; steroid and terpenoid testing; flavonoid test; saponin test; phenolic hydroquinone; tannin and polyphenol test. Based on phytochemical test results, the extract of patat leaves was known to contain alkaloids, steroids, triterpenoids, flavonoids, saponins, phenolic hydroquinones, and tannins with different distributions at each level of solvent polarity. The instruments used to identify the chemical content of patat leaf extract were GCMS and LCMS QTOF. Through GCMS analysis on n-hexane extract, 114 compounds were identified with a similarity level of ≥ 80% to the library. Among these compounds, confirmed to be terpenoid and steroid compounds. In the LCMS analysis of ethyl acetate extract obtained 25 compounds and 31 compounds for methanol extract. It is suspected that these compounds come from the alkaloid, steroid, flavonoid, saponin, phenolic hydroquinone, or tannin class.